Matrix-free human lung organoids derived from induced pluripotent stem cells to model lung injury - Bettina Budeus; Chiara Kroepel; Lisa Marie Stasch; Diana Klein (Stem Cell Research & Therapy)
Abstract Background Organoids, as near-physiological 3D culture systems, offer new opportunities to study the pathogenesis of various organs in mimicking the cellular complexity and functionality of human organs. Method Here we used a quite simple and very practicable method to successfully generate induced pluripotent stem cell (iPSC)-derived human lung organoids (LuOrg) in a matrix-free manner as an alternative to the widely used preclinical mouse models in order to investigate normal lung damage in detail and as close as possible to the patient. We performed detailed morphological and molecular analyses, including bulk and single cell RNA sequencing, of generated lung organoids and evaluated the quality and robustness of our model as a potential in vitro platform for lung diseases, namely radiation-induced lung injury. Results A matrix-free method for differentiation of iPSCs can be used to obtain lung organoids that morphologically reflect the target tissue of the human lung very well, especially with regard to the cellular composition. The different cellular fates were investigated following the genotoxic stress induced by radiation and revealed further insights in the radiation-sensitivity of the different lung cells. Finally, we provide cellular gene sets found to be induced in the different lung organoid cellular subsets after irradiation, which could be used as additional RT response and particularly senescence gene sets in future studies. Conclusion By establishing these free-floating LuOrgs for the investigation of cancer therapeutic approaches as a new and patient-oriented in vitro platform particularly in experimental radiooncology, not only a reduction in the number of experimental animals, but also an adequately and meaningfully replacement of corresponding animal experiments can be achieved.